2019
DOI: 10.1371/journal.pone.0220789
|View full text |Cite
|
Sign up to set email alerts
|

Failures in the case management of children with uncomplicated malaria in Bata district of Equatorial Guinea and associated factors

Abstract: Background In Equatorial Guinea, malaria continues to be one of the main causes of morbidity and mortality among children. The National Therapeutic Guide established artesunate-amodiaquine (ASAQ) as first-line treatment for uncomplicated malaria, but compliance with this treatment is low. The aim of this study was to assess, for the first time, the performance of public healthcare workers in the diagnosis and treatment of uncomplicated malaria, their compliance with first-line Malaria National The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The same reasons and preference for AL compared to ASAQ has been described in many countries in the region [ 25 , 26 ]. The use of injectable AM as a treatment for uncomplicated malaria has only been described in Sudan [ 27 , 28 ] and Equatorial Guinea [ 15 , 29 ]. This use of artemisinin monotherapy to treat uncomplicated malaria can contribute to the emergence of resistance to ACT and lead to treatment failure [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same reasons and preference for AL compared to ASAQ has been described in many countries in the region [ 25 , 26 ]. The use of injectable AM as a treatment for uncomplicated malaria has only been described in Sudan [ 27 , 28 ] and Equatorial Guinea [ 15 , 29 ]. This use of artemisinin monotherapy to treat uncomplicated malaria can contribute to the emergence of resistance to ACT and lead to treatment failure [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Questions about their sociodemographic characteristics, the biological cycle of malaria parasites, malaria treatment practices, the recommendations given by the NMTG and resistance to anti-malarial drugs were included in the questionnaire. Details of the survey have been described previously [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies in Sudan identified relatively high proportions of children with uncomplicated malaria receiving injectable quinine [36], but with receipt of injectables more frequent in those over five than under 5 years [37]. Monotherapy was also more common in those aged older than five in studies in Nigeria [15] and Equatorial Guinea [18]. When monotherapy is prescribed for severe malaria, parenteral drugs should be given for a minimum of 24 h and always followed by a full oral course of ACT [4,38].…”
Section: Discussionmentioning
confidence: 99%
“…Limitations in case management identified by previous studies included failure to perform diagnostic testing on all suspected malaria cases [13][14][15], prescription of antimalarial drugs for test negative patients [14,16,17], or ACT not being prescribed to patients with confirmed malaria [18,19]. Additional shortcomings in other settings include 'poly-pharmacy' whereby multiple antimalarials are given at once, incorrect dose prescription [13,20], and lack of referral/admission or pre-referral treatment for severe malaria [21].…”
Section: Introductionmentioning
confidence: 99%